Characteristics of coupled orbital-attitude dynamics of flexible electric solar wind sail. (June 2019) - Li, Gangqiang; Zhu, Zheng H.; Du, Chonggang; Meguid, S.A.
Abstract: This paper studies the dynamic characteristics of an electric solar wind sail (E-sail). A high-fidelity multiphysics model is developed by the nodal position finite element method to investigate the coupling effects of orbital and self-spinning motions of the E-sail, and the interaction between the axial/transverse elastic motions of tether and the Coulomb force. Furthermore, parametric study is conducted to better understand these coupling effects. The simulation results show that the coupling effects have a significant impact on the dynamic behavior of E-sail and the induced thrust. Furthermore, the analysis indicates a strong dependence of the thrust on sail and coning angles of E-sail even in the case of small sail angle. Finally, the influence of the initial self-spin rate and the sail angle on the dynamic behavior of a flexible E-sail is investigated. It shows that a high spin rate is needed to hold the geometrical configuration of the E-sail, and the difference in the orbital maneuvering is distinct when the E-sail inclines to the incident solar wind. It implies that a suitable control strategy should be employed to accomplish the thrust vectoring for the orbit maneuvering. The analysis provides an effective and robust way to design the E-sail in the mission planning phase. Highlights: Developed high-fidelity multiphysics model for electric solar wind sail. Revealed coupling effect of orbital and self-spin motion of E-sail. Studied interaction between axial/transverse motion of tether and Coulomb force. Studied influence of initial self-spin rate & sail angle on flexible E-sail dynamics. High spin rate is needed to hold the geometrical configuration of E-sail.